Review Penelitian Kanker Paru di Indonesia - Ratih Oemiati (Jurnal Persada Husada Indonesia, 2015)
World Health Organization (WHO) indicated that lung cancer is the leading cause of death in men and women. In Indonesia, lung cancer ranks third or fourth among cancer malignancy. Lung cancer is generally found in middle age and elderly. Ratio of lung cancer is 2:1 for male and female with adenocarcinoma as the highest of pathology anatomy. This paper is the result of a study of lung cancer research and literature review in Indonesia. The aim of this research is to explore retrospective and cohort study of lung cancer using descriptive analysis. The mean of each variable was measured repeatedly to determine the result. The retrospective data showed that sex ratio was 3,5 with 30 years old for the youngest and the oldest was 72 years old. Most of them were in third stadium, and squamosal cell was the most common type of lung cancer. Cohort study described that sex ratio was 5,8 with 37 years old for the youngest and the oldest was 73 years old and the average age was 55 years. The most common respondents were in the third stadium (40 people). The most common lung cancer similar to retrospective study was squamosal cell.